Can home-made injectable opiates contribute to the HIV epidemic among injection drug users in the countries of the former Soviet Union? - Abdala, Nadia; Grund, Jean-Paul C; Tolstov, Yanis; Kozlov, Andrei P; Heimer, Robert (Addiction (Abingdon, England), 2006)
Home-made preparation of heroin is common in countries of the former Soviet Union (FSU), and the addition of blood during its preparation and the use of contaminated syringes to distribute it may play a role in the rapid spread of HIV-1 among injecting drug users (IDUs). This study was designed to determine the viability of HIV-1 during these procedures.
Keywords: Disease Outbreaks; Drug Design; HIV Infections; HIV-1; Humans; Narcotics; Needle Sharing; Opioid-Related Disorders; Risk-Taking; Substance Abuse, Intravenous; USSR